2015
DOI: 10.1515/ohs-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Leeches (Clitellata: Hirudinida) of an upland stream: taxonomic composition in relation to habitat conditions

Abstract: I n t e r n a t i o n a l J o u r n a l o f O c e a n o g r a p h y a n d H y d r o b i o l o g y AbstractHirudinida comprise a constant component of benthofauna in running waters and their taxonomic composition is often analyzed to evaluate the environmental quality. However, the indicatory role of particular species is still arguable. Thus, it is very important to provide more detailed information on the impact of environmental parameters on the species structure within this group of invertebrates. Represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…They are top predators and ectoparasites that control prey and host populations in spring ecosystems. At the same time, leeches are prey for many carnivorous species (Koperski, 2006;Kubová et al, 2013;Cichocka et al, 2015;Živić et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are top predators and ectoparasites that control prey and host populations in spring ecosystems. At the same time, leeches are prey for many carnivorous species (Koperski, 2006;Kubová et al, 2013;Cichocka et al, 2015;Živić et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical variables of water, substrate type and food availability are the main factors determining the distribution patterns of free-living leeches (Koperski, 2006(Koperski, , 2010Beracko and Ko sel, 2011;Kubová et al, 2013;Cichocka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that in these cases, the combination of the faster-flowing and higher saprobic state has favored E. vilnensis in competition with other species. Many articles support the conclusion that E. vilnensis prefers smaller water bodies located at medium-high and higher altitudes [55,57,58].…”
Section: Discussionmentioning
confidence: 93%
“…These rivers are under anthropogenic pressures, and are often exposed to water quality degradation [53,54]. Tolerance to mesosaprobic conditions is known in the case of E. vilnensis [48,55,56]. It can be concluded that in these cases, the combination of the faster-flowing and higher saprobic state has favored E. vilnensis in competition with other species.…”
Section: Discussionmentioning
confidence: 99%
“…Kazancı et al 2015) and in most biomonitoring protocols they are treated as negative bioindicators. However, the response of their diversity to pollution and the increase in nutrients load is not easy to interprete, because particular leech species distinctly differ in environmental preferences (Koperski 2005(Koperski , 2006(Koperski , 2017Kubova et al 2013;Cichocka et al 2015). Basic abiotic parameters seem to be clearly correlated with the taxonomic structure of lotic leech assemblages (Kubová and Schenkova 2014;Jabłońska-Barna 2017).…”
Section: Discussionmentioning
confidence: 99%